2010
DOI: 10.1186/1753-4631-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Simple fractal method of assessment of histological images for application in medical diagnostics

Abstract: We propose new method of assessment of histological images for medical diagnostics. 2-D image is preprocessed to form 1-D landscapes or 1-D signature of the image contour and then their complexity is analyzed using Higuchi's fractal dimension method. The method may have broad medical application, from choosing implant materials to differentiation between benign masses and malignant breast tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
(10 reference statements)
1
14
0
Order By: Relevance
“…12a), DNA sequencing, and long-range anticorrelations in heartbeat regulation or rhythm (Havlin et al 1995). Fractal shapes and fractal analysis have also been applied to the identification of tumors in brain MR images and other histological images in medical diagnostics (Klonowski et al 2010). Fractal antennas, which use selfsimilar design to maximize material structures which receive or transmit electromagnetic radiation, produce compact, multiband, or wideband antennas used in cell phone and other microwave applications.…”
Section: Branched Systems and Fractal Structuresmentioning
confidence: 99%
“…12a), DNA sequencing, and long-range anticorrelations in heartbeat regulation or rhythm (Havlin et al 1995). Fractal shapes and fractal analysis have also been applied to the identification of tumors in brain MR images and other histological images in medical diagnostics (Klonowski et al 2010). Fractal antennas, which use selfsimilar design to maximize material structures which receive or transmit electromagnetic radiation, produce compact, multiband, or wideband antennas used in cell phone and other microwave applications.…”
Section: Branched Systems and Fractal Structuresmentioning
confidence: 99%
“…29 However, unusual cases exist of benign masses that have macrolobulated or spiculated contours as well as of malignant tumors that have smooth or microlobulated boundaries without spicules. Klonowski et al 35 applied Higuchi's method for fractal analysis of the texture seen in histological images as well as for the analysis of the shape of breast masses. Matsubara et al 34 reported 100% accuracy in the classification of a small dataset of 13 benign masses and malignant tumors using FD.…”
Section: Shape Characteristics Of Breast Massesmentioning
confidence: 99%
“…15,30,35,[37][38][39][40][41] Regardless, several studies have shown that shape factors perform better in discriminating between benign masses and malignant tumors than other measures related to breast density, contrast, texture, and edge sharpness. For these reasons, CAD systems and algorithms need to use combinations of several features derived from various images or regions related to breast masses; it is common to use many measures representing not only shape but also texture, density, and edge sharpness.…”
Section: Shape Characteristics Of Breast Massesmentioning
confidence: 99%
“…For these tasks, determining the fractal dimensions of 2D digital images has been very successful in recent years [12,13,14,15,16]. The methods involved include the well known Box counting method or the Minkowski dilation method.…”
Section: Introductionmentioning
confidence: 99%